Geometric Ring Annuloplasty for Aortic Valve Repair During Aortic Aneurysm Surgery: Two-Year Clinical Trial Results - Rankin, J Scott; Mazzitelli, Domenico; Fischlein, Theodor; Choi, Yeong-Hoon; Pirk, Jan; Pfeiffer, Steffen; Wei, Lawrence M; Badhwar, Vinay (Innovations (Philadelphia, Pa.), 2018)
OBJECTIVE: An aortic annuloplasty ring could be useful for aortic valve repair. This trial evaluated intermediate-term outcomes of internal geometric ring annuloplasty for repair of trileaflet and bicuspid aortic insufficiency associated with ascending aortic and/or aortic root aneurysms. METHODS: Under regulatory supervision, 47 patients with aortic insufficiency and ascending aortic (n = 22) and/or aortic root (n = 25) aneurysms were managed with aortic valve repair and aneurysm resection. Valve repair was performed using trileaflet (n = 40) or bicuspid (n = 7) internal geometric rings, together with leaflet reconstruction. Ascending aortic and/or remodeling root replacements were accomplished with Dacron grafts 5 to 7 mm larger than the rings. An Echo Core Lab provided independent echocardiographic assessments, and changes over time were evaluated by Friedman tests. RESULTS: Mean ± SD age was 60 ± 14 years, 57% (27/47) were male, 15% (7/47) had bicuspid valves, 87% (41/47) had moderate-to-severe aortic insufficiency, and 13% (6/47) had mild aortic insufficiency. All patients had annular dilatation, with a mean ± SD of 26.5 ± 2.6 mm before repair, and mean ± SD ring sizes were 21.7 ± 1.7 mm. Follow-up was 42 months (mean = 27 months). No operative mortality or valve-related complications occurred. Two patients died beyond 1 year from nonvalve-related causes. One patient required valve replacement for repair failure. Survival free of complications or valve replacement was 94% at 2 years. Significant reduction in aortic insufficiency and New York Heart Association class were observed (P < 0.0001), and valve gradients remained low. No heart block or direct ring complications occurred. CONCLUSIONS: In preliminary regulatory studies, aortic ring annuloplasty seemed safe and effective during aortic aneurysm surgery. This approach could help standardize aortic valve repair.
Keywords: aortální aneurysma; dospělí; Cardiac Valve Annuloplasty; Female; Prosthesis Design; anuloplastika srdeční chlopně; aortální chlopeň; Adult; protézy - design; ženské pohlaví; srdeční chlopně umělé; lidé; Heart Valve Prosthesis; pooperační komplikace; Reoperation; reoperace; Male; Postoperative Complications; Aged; Aortic Valve; lidé středního věku; senioři; mužské pohlaví; Middle Aged; Aortic Aneurysm; Humans